2021
DOI: 10.3390/ijerph182010580
|View full text |Cite
|
Sign up to set email alerts
|

Work Task Association with Lead Urine and Blood Concentrations in Informal Electronic Waste Recyclers in Thailand and Chile

Abstract: The informal recycling of electronic waste (“e-waste”) is a lucrative business for workers in low- and middle-income countries across the globe. Workers dismantle e-waste to recover valuable materials that can be sold for income. However, workers expose themselves and the surrounding environment to hazardous agents during the process, including toxic metals like lead (Pb). To assess which tools, tasks, and job characteristics result in higher concentrations of urine and blood lead levels among workers, ten ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…La implementación de intervenciones focalizadas en estos factores podría contribuir a la reducción de los niveles de Pb en los trabajadores informales del reciclaje de residuos electrónicos. Además, para futuras investigaciones, se sugiere evaluar metales tóxicos distintos del Pb y considerar las exposiciones a múltiples metales (Shkembi, et al, 2021).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…La implementación de intervenciones focalizadas en estos factores podría contribuir a la reducción de los niveles de Pb en los trabajadores informales del reciclaje de residuos electrónicos. Además, para futuras investigaciones, se sugiere evaluar metales tóxicos distintos del Pb y considerar las exposiciones a múltiples metales (Shkembi, et al, 2021).…”
Section: Resultsunclassified
“…Mientras que en Bogotá se identifican riesgos físicos como temperaturas extremas (Rojas & Vásquez, 2020), en Sao Paulo, Brasil, la exposición a concentraciones de mercurio es una preocupación destacada (Gouveia, et al, 2019). En Chile, se abordan los riesgos asociados a la exposición al plomo, señalando la necesidad de intervenciones focalizadas en factores específicos (Shkembi, et al, 2021).…”
Section: Discussionunclassified
“…A study by Hwang [ 30 ] corroborates this, discovering that BLLs in children in very high HDI countries were lower than countries with lower HDI levels, which explains the variation in BLLs in pregnant women across different countries. Previous studies in Thailand, primarily focused on worker and children’s groups, showed that the factors related to BLLs included occupation, environment, and living near factory plants or fishing communities [ 17 , 31 , 32 , 33 , 34 ]; however, there were no data concerning factors related to BLLs in pregnant women. In this study, we examined demographic factors, consumer goods factors, and supplement intake factors.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of public awareness of the hazardous nature of e-waste and proper disposing/handling mechanisms are the few other reasons for irresponsible behaviour [ 13 , 27 , 55 ]. The public is considering e-waste as regular solid waste and mix with other household waste, throw away in unoccupied areas, burning, and burying are some of the major practices, which eventually contribute to environmental and human hazards rather than informal urban mining [ 56 ]. The challenges were compounded by handing over residential, business, and institutional e-waste to informal collectors.…”
Section: Strategies To Enhance E-waste Management In South-asiamentioning
confidence: 99%